Antenatal Clinic Waiting Time, Patient Satisfaction, and Preference for Staggered Appointment–A Cross-Sectional Study - RA Abdus-salam (SAGE Publishing, 2021)
Time spent in the antenatal clinic (ANC) is a major disincentive for pregnant women and constitutes a barrier to the utilization of ANC. Long waiting time and poor patient satisfaction may contribute to poor utilization. This study assessed waiting time, patients’ satisfaction, and preference for staggered ANC appointments. A cross-sectional study was conducted; information obtained includes sociodemographic and obstetric characteristics, and time spent at ANC service points. Data were analyzed using International Business Machines (IBM) Statistical Products and Service Solutions (SPSS) software version 23. Descriptive statistics and chi-square test were conducted. Level of significance: P  < .05. One hundred and twenty-two participants were interviewed. Mean age was 30.52 (±4.65) years, they were mostly multi-gravid, married, and with tertiary education. Mean time spent in ANC and waiting time were 191 min and 143 min, respectively. Waiting time was longest at doctor's consultation (59 min), laboratory services (38 min), and the cash pay-point (18 min). About 68.9% were satisfied with services and highest at doctors’ consultation. Satisfaction was associated with waiting time of <45 min. Dissatisfaction was high at the cash pay-point (28.7%), followed by the laboratory (16.4%). About 56.5% preferred staggered appointments. Time spent in ANC should be reduced and staggered appointments may be a useful strategy to reduce waiting time and patient load.